Building capacities of African agribusinesses on impact measurement. A Knowledge, Awareness, Skills, and Practice (KASP) Study - Nowak, Andreea C. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
This report outlines the methodology and findings of the Knowledge, Awareness, Skills, and Practices (KASP) study, which evaluated the impact of a capacity-building program aimed at enhancing agribusiness capacities under the AICCRA project. The study assessed how the program contributed to improving the ability of agribusinesses across two Accelerator Program cohorts— the CGIAR Food System Accelerator (FSA) and the Rwanda Adaptation Accelerator Program (RAAP)—to understand, measure, and manage impacts in the context of climate change. Using baseline and endline surveys, alongside qualitative feedback, the study measured changes in agribusiness capacities, evaluated the effectiveness of the training sessions, and identified areas for further support. The findings demonstrate that both cohorts saw significant improvements in knowledge, attitudes, skills, and practices related to impact measurement, with a marked increase in technical capabilities, especially among FSA participants who started at a lower baseline. At the endline, 84% of respondents reported improved knowledge, with most participants showing gains in impact measurement tools, particularly in applying impact pathways and indicators. Attitudes toward the program were overwhelmingly positive, with participants recognizing its relevance and practical value. Skills in climate risk assessment and impact measurement increased substantially, particularly for FSA participants. While the adoption of impact measurement practices increased in both cohorts, the more substantial gains in FSA highlight the program's success in supporting participants with lower baseline knowledge. These findings suggest that the training not only enhanced technical capabilities but also fostered more structured and intentional impact measurement practices. Furthermore, the program successfully transitioned participants from being passive receivers of information to active users of the knowledge and tools gained. This shift signifies a deeper integration of impact measurement practices into participants' approaches, enabling them to use the acquired skills and tools to inform decision-making and drive change within their organizations. However, some challenges remained, particularly for more advanced users who may benefit from further refinements in future sessions. The study emphasizes the importance of continued support, localized examples, and practical tools to ensure that learning is integrated effectively into diverse business contexts. The findings also underline the potential for future iterations of the program to address gaps in knowledge and provide more targeted technical assistance to maximize impact.